Attitude for success (Menlo Park, Calif. : Crisp Learning, 2001)
This cd-rom program define the components of attitude, leraning skills for adjusting our attitude and understanding the benefits of a good attitude
This self-directed learning package includes Window compatible CD and fifty-minute series workbook
Workbook title : Attitude : your most priceless possession
System requirements : Windows 95/98 or later or Windows NT 4 or later ; Pnetium 133 MHz processor or equivalent; 32 MB or Memory (RAM); 4x CD-ROM drive; 16 bit sound card and speakers; High color (16 bit) display; 800 x 600 monitor resolution
Keywords: Attitude (Psychology)